AUDIT REPORT QUALITY, SUSTAINABILITY AND PROFITABILITY ON STOCK PRICE IN INDONESIA SECURITIES EXCHANGE - Sekar Mayangsari; Try Edi Suwarno (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study examines the relationship between audit reports, sustainability reports, and profitability to stock prices on the Indonesia stock exchange, especially manufacturing companies in the basic industrial and chemical sectors, miscellaneous industrial sectors, and consumer goods industry sectors. Secondary data is generated through audit reports and sustainability reports provided in a structured manner. The population for this study consisted of 211 company populations using 16 samples of manufacturing companies that published audited financial reports and sustainability reports in 2019-2021. The hypothesis was tested using the Multiple Linear Statistical Test. The test was conducted at a significance level of 0.05. The findings of this study reveal that there is a significant relationship between profitability and stock price. Meanwhile, audit reports and sustainability reports do not provide a relationship to stock prices on the Indonesia Stock Exchange. This study recommends increasing the educational aspects of the capital market and investment for the Indonesian people, especially investors, so that it will slowly increase the knowledge of investors and potential investors in Indonesia about the importance of audit reports and sustainability reports.